A short history of the Tudors. By Richard Rex. (Short Histories.) Pp. 213. London-New York: Bloomsbury Academic, 2024. £14.99 (paper). 978 1 350 17042 1 - Donnelly, Colin Michael (The journal of ecclesiastical history, 2025)
A short history of the Tudors. By Richard Rex. (Short Histories.) Pp. 213. London-New York: Bloomsbury Academic, 2024. £14.99 (paper). 978 1 350 17042 1 - Volume 76 Issue 3